Unburdening the Shoulders of Giants: A Quest for Disconnected Academic Psychology. (July 2020) - Krpan, Dario
In current academic psychology, scholars typically develop their research and ideas by drawing on the work of other contemporary and preceding psychological scientists and by following certain conventions of the field. I refer to this variant of psychology as connected because the emphasis is on connecting various research findings and ideas generated by different scholars (e.g., by showing how they are related to each other via referencing). In this article, I argue that, although connected psychology advances psychological knowledge, it restricts the total amount of knowledge that could eventually be produced and therefore limits the potential of the discipline to improve the understanding of psychological phenomena. As a solution, I propose that, alongside the currently existing connected psychology, disconnected psychology should be established. In disconnected psychology, researchers develop their ideas by following the main principles of psychological method, but they are disconnected from a "field" consisting of other psychologists and therefore do not follow the discipline's norms and conventions. By drawing on one of the core constructs from information theory—information entropy—I argue that combining the two streams of psychology would result in the most significant advancement of psychological knowledge.